Efektivitas Program Comprehensive Guidance and Counselling terhadap Pembentukan Karakter Tanggung Jawab Remaja dalam Pendidikan Formal - Ikhwal Octahabriansyah; Triono Ali Mustofa (LP. Ma'arif Janggan Magetan, 2023)
Education in the 21st century emphasizes not only the quality of learning and academic achievements but also the formation of student character. Although character education has become a primary focus in recent decades, its implementation is often overlooked, especially in Indonesia. In the context of formal education in schools, there is an imbalance between academic competence and character development. To address this imbalance, the Comprehensive Guidance and Counselling (CGC) program is expected to bridge between academic achievement and character formation. This research focuses on the implementation and effectiveness of the CGC program in shaping the character of responsibility at Muhammadiyah Al-Kautsar Junior High School. Using a descriptive qualitative method with a phenomenological approach, the results show that the CGC program has had a positive impact on the formation of students' responsibility character. Support from various parties is key to the successful implementation of this program, but there are also challenges, especially related to the influence of social media and mental health issues among teenagers. This research is expected to contribute to character education literature and serve as a reference for educational practitioners in Indonesia..